Levantamiento de procesos en el área de logística de la empresa importadora Alvarado - Erazo Dias, Jonathan Mauricio (2024)
This research was conducted in the company "IMPORTADORA ALVARADO CÍA. LTDA.", located in the city of Ambato, province of Tungurahua in the Industrial Park, specifically in the logistics area, which is responsible for the allocation, shipment, and distribution of auto parts nationwide. The company does not have a process manual for the logistics area, since it is in constant growth, the absence of it generates delays, mistakes, repeated activities, and loss of merchandise. The main objective of this project is the development of a proposal for a process manual, the method used was the cascade model to record the activities that are developed, in the same way the technique of the survey was used, the results obtained show that the processes are known empirically; the following processes were analyzed: Load assignment, truck loading, policy of withdrawal of packages and cancellation of orders, it was concluded through the tools such as the analytical chart that the process of loading trucks is the longest and takes an average of 14340s. With this information, the manual of processes and procedures of the logistics area was generated. It is concluded that the manual is essential in the development of operations since it guides each activity which ensures a progressive flow of work, also establishes clear rules, and serves as a basis for future research seeking to optimize processes.